Primary hyperparathyroidism: Increasing prevalence, social deprivation, and surgery. (2nd January 2017) - Collier, Andrew; Portelli, Mark; Ghosh, Sujoy; Nowell, Sian; Clark, David
ABSTRACT: Objective : To measure the increasing incidence of primary hyperparathyroidism (PHPT) in Scotland, to determine the relationship between PHPT and deprivation, and to investigate the relationship between parathyroidectomy (PTX) and social deprivation.Methods : We retrospectively identified a cohort of patients diagnosed with PHPT between 1986 and 2013 from the Scottish Morbidity Records (SMR01) database. The diagnosis of PHPT was made in accordance with the International Classification of Diseases code.Results : Between the years 1986 and 2013, 4002 patients were diagnosed with PHPT. There was a significant increase in the incidence of PHPT in this period ( p < 0.0001), an association between the incidence of PHPT and deprivation ( p < 0.0001) plus an association between a lower rate of PTX and deprivation ( p < 0.001).Conclusion : The increase in incidence of PHPT may be due to a combination of increased awareness of PHPT, easier diagnosis, and an ageing population. The lower rate of PTX in relation to deprivation may reflect comorbidities, age, and uncertainty about the long-term benefits of PTX in asymptomatic patients.